Knowledge of the Unknown in the Known World - Isanbor, Philip Osarobu; Folorunso, Paul Olorunsola (NIU Journal of Humanities; Vol 6 No 2 (2021): KIU Journal of Humanities, Vol. 6 No. 2, June 2021, 2021)
Within the power and influence of human reasoning, the known world recognizes that there are many things that can be known. It rationally professed already and yet unknown, the metaphysical, to be beyond the subjection of the principles and workability of verification. The paper is to assess the indispensability of the knowledge of what claimed to be unknown in our known world. This conviction of certainty will always goes with these questions: within the known World of experience, can one separate the scientific conviction from the foundational influences of metaphysics? Is the human person solely metaphysical or experiential? The answers to these questions remain always dilemmatic but reasonable in our highly motivated relativistic world. Here, the emphasis is strongly on the knowledge of God which has always appeared very elusive to human sense of methodological verifiability, but remains very conspicuously factual within the interaction of faith and reason. With the interplay of faith and reason, the paper posits that everything is known, and there is nothing like no-thing in a known world; since nothing is something. It paper owes that knowing nothing as â€œnothingâ€ is something; since it is already known as nothing. With the truth inherent in human nature, this somehow and sometimes ascertains the possibility of knowing the claimed â€˜unknownâ€™, overwhelmed the principles and practicability of verification, there is always a justification of any knowledge claimed, even in the known world surnamed by scientific and technological consciousness, since reasoning within the power of human rationality and intelligibility cannot be disputed. Keywords : God, Knowledge, Verification, Science, Faith, Reason, Intelligibility